Pengaruh Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Sebagai Variabel Intervening (Studi Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kabupaten Kolaka Timur) - Haslia Haslia; Ibnu Hajar; Muhammad Masri; Nursaban Rommy (Pascasarjana Universitas Halu Oleo, 2021)
The purpose of this study was to examine and explain the influence of leadership and work environment on employee performance through job satisfaction as an intervening variable (study on the staffing agency and human resource development in East Kolaka Regency). Data collection is done by using a questionnaire and documentation. The population of this study were employees of the personnel and human resource development agency in East Kolaka Regency, with the method of determining the census, so that the sample size was set at 51 employees. The analytical tool used is SmartPLS.The results showed that leadership had a positive and insignificant effect on employee job satisfaction. Leadership has a positive and significant impact on employee performance. The work environment has a positive and significant influence on employee job satisfaction. The work environment has a positive and significant impact on employee performance. Job satisfaction has a positive and insignificant effect on employee performance. Job satisfaction does not play a role in mediating the influence of leadership on employee performance. Job satisfaction plays a role in mediating the influence of the work environment on employee performance.